A synopsis of the process of lipid peroxidation since the discovery of the essential fatty acids - Catala, Angel (2010)
Eighty years ago, Burr and Burr, introduced for the ﬁrst time the concept of essential fatty acids. Now is very well known that requirements for polyunsaturated fatty acids PUFAs can not be met by de novo metabolic processes within mammalian tissues. Animals are absolutely dependent on plants for providing the two major precursors of the n-6 and n-3 fatty acids, C18:2n-6; linoleic and C18:3n-3; a-linolenic acids. In animal tissues these precursors are transformed to fatty acids containing three to six double bonds. During the last four decades the interest in polyunsaturated fatty acids has augmented manifolds, and the number of published studies is rising each year. The current impetus for this interest has been mainly the observation that PUFAs and their metabolites have several physiological roles including: energy provision, membrane structure, cell signaling and regulation of gene expression. In addition the observation that PUFAs are targets of lipid peroxidation opens a new important area of investigation. Melatonin, the main secretory product of the pineal gland, efﬁciently scavenges both the hydroxyl and peroxyl radicals counteracting lipid peroxidation in biological membranes. In addition the two key pineal biochemical functions, lipoxygenation and melatonin synthesis may be synergistically regulated by the status of n-3 essential fatty acids. At the retina level, free radicals may preferentially react with the membrane polyunsaturated fatty acids leading to the release of lipoperoxide radicals. These lipoperoxides can induce oxidative stress linked to membrane lysis, damage to neuronal membranes may be related to alteration of visual function.